#TITLE_ALTERNATIVE# - SETIAWAN (NIM 22205001), DODI
Nowadays, waterflooding become a secondary recovery stage which is implemented by many oil fields. Knowledge of waterflooding efficiency depends on the understanding level about the reservoir characterization. This can be obtained statically by a geology examination and dynamically by the study of reservoir engineering, which can be procured by well testing. The analysis of injection well testing has been done by many researchers. Some of them made an assumption that mobility ratio (M), which is the ratio of the mobility of injected fluid with the mobility of reservoir fluid is unit1. By this assumption, we can approach the analysis of injection well testing by the analysis of production well testing. The injectivity, that is when a well is injected with a constant water injection or constant pressure can be approached with drawdown. The analysis of buildup well testing can be applied to analyze falloff testing, that is when a well after injected in a certain time, then the well is closed for a certain time. This thesis evaluated some of falloff well testing analysis methods that doesnÃƒÂ‚Ã‚Â’t assume the unit mobility ratio. Those methods are HazebroekÃƒÂ‚Ã‚Â–RainbowÃƒÂ‚Ã‚Â–Matthews (HRM)2, which determines the value of Pe on log (PwsÃƒÂ‚Ã‚Â–Pe) vs shut in time(Δt) plot by trial and error procedure; MerrilÃƒÂ‚Ã‚Â–KazemyÃƒÂ‚Ã‚Â–Gogarty (MKG)3, which including the saturation gradation which is caused by the differential characteristics of injected and original reservoir fluids; L.P. Brown4 also calculating the gradual saturation with correction that is storage ratio doesnÃƒÂ‚Ã‚Â’t affecting the slope of second line pressureÃƒÂ‚Ã‚Â–time semilog plot. With commercial simulatorÃƒÂ‚Ã‚Â’s help, these analytical methods are evaluated by a model which is validated with actual field data. This evaluation covered the sensitivity of injection time, viscosity and compressibility of oil, and also formation permeability. The result from MKG and Brown gave the value of permeability that close enough with the input. On the other hand, HRM gave more pessimistic value. In the determination of skin factor, MKG and Brown gave similar value even though through different approach. MKGÃƒÂ‚Ã‚Â’s approach only based on the characteristic of zone 1 fluids, BrownÃƒÂ‚Ã‚Â’s based on both zone fluids with weighted on zone 2. But both methods gave the result which is far enough to the input. The result of HRM method gave the value which is closer to the input. The fluid front of zone 1 and 2 that resulted from both intersection time equation of MKG and material balance equation of HRM is similar. The value from Brown is quite different. This can be caused by the specific storage ratio which affected the fluid front.